2019
DOI: 10.1177/2047487319829746
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing for familial hypercholesterolemia: Impact on diagnosis, treatment and cardiovascular risk

Abstract: Aims Familial hypercholesterolemia (FH) is the most common genetic disorder in medicine, with a prevalence of 1/250. Affected individuals have elevated low-density lipoprotein cholesterol (LDL-C) and an increased lifetime risk of atherosclerotic cardiovascular disease (ASCVD). The diagnosis of FH is based on algorithms that include LDL-C levels, physical manifestations, family history of high LDL-C and premature ASCVD, and, more recently, genetic testing. We sought to determine the impact of genetic testing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Our findings are consistent with a recent systematic review and meta-analysis showing that FH genetic testing can confirm FH diagnosis over clinical criteria alone, depending on the diagnostic algorithm and the method of analysis [41]. However, given that eight of the 21 studies reviewed reported only two non-clinical outcomes (education on lifestyle management and genetic counseling) following FH genetic testing, with no particular consistency in reporting these outcomes, there is opportunity to determine broader, non-clinical outcomes following FH genetic testing (e.g., behavioral outcomes like statin treatment adherence).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with a recent systematic review and meta-analysis showing that FH genetic testing can confirm FH diagnosis over clinical criteria alone, depending on the diagnostic algorithm and the method of analysis [41]. However, given that eight of the 21 studies reviewed reported only two non-clinical outcomes (education on lifestyle management and genetic counseling) following FH genetic testing, with no particular consistency in reporting these outcomes, there is opportunity to determine broader, non-clinical outcomes following FH genetic testing (e.g., behavioral outcomes like statin treatment adherence).…”
Section: Discussionsupporting
confidence: 92%
“…Dutch Lipid Clinic Network (DLCN) criteria), ideally followed by DNA sequencing to identify variants in the LDLR, APOB and PCSK9 genes that cause FH. A genetic diagnosis of FH allows better CVD risk stratification, 2 increases therapy adherence of the diagnosed patient 3 and allows cascade testing of first-degree relatives. 4 Apart from the three canonical FH genes, pathogenic variants in other so-called 'minor FH' genes may also contribute to or mimic the FH phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of genetic background of the FH becomes important nowadays because particular mutations were reported to affect phenotype of patients and due to new possibilities of treatment [ 33 37 ]. Unfortunately, no significant association between presence of presumed pathogenic gene variants and aggravation of atherosclerosis was observed.…”
Section: Discussionmentioning
confidence: 99%